Agricultural extension, rural development and the food security challenge / ?c William McLeod Rivera in collaboration with M. Kalim Qamar. - Rivera, William McLeod; Qamar, M. Kalim; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2003)
Reviews the major trends to reform agricultural extension systems, discusses rural development, examining pathways out of poverty, and advocates a broader role for extension. The continuing and unique role to be played by the public sector in promoting rural development through extension and communication is highlighted. Important conclusions, drawn from the analysis of relevant issues, as well as action-oriented recommendations, are presented to the policy-makers of developing countries for encouraging institutional reforms.
Includes bibliographical references .
1
Keywords: Food supply -- Government policy -- Developing countries; Nutrition extension work -- Developing countries; Agricultural extension workers; Agriculture and state -- Developing countries; Agricultural extension work -- Developing countries